2019
DOI: 10.3847/2041-8213/ab2f91
|View full text |Cite
|
Sign up to set email alerts
|

Automated Detection of Rapid Variability of Moss Using SDO/AIA and Its Connection to the Solar Corona

Abstract: Active region moss-the upper transition region of hot loops-was observed exhibiting rapid intensity variability on timescales of order 15 s by Testa et al. in a short time series (∼150 s) data set from Hi-C (High-resolution Coronal Imager). The intensity fluctuations in the subarcsecond 193A images (∼1.5 MK plasma) were uncharacteristic of steadily heated moss and were considered an indication of heating events connected to the corona. Intriguingly, these brightenings displayed a connection to the ends of tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…However, we are now working on follow-up work which will allow us to overcome this shortcoming, by using automated detection. Graham et al (2019) recently presented an algorithm, improved from the one we used on Hi-C data (Testa et al 2013), which allows us to automatically detect rapid moss variability in AIA timeseries. We are currently working on applying this algorithm to AIA datacubes co-aligned with IRIS data (already available on the IRIS data search webpage 3 ), to automatically find these brightenings in IRIS spectral data.…”
Section: Discussionmentioning
confidence: 99%
“…However, we are now working on follow-up work which will allow us to overcome this shortcoming, by using automated detection. Graham et al (2019) recently presented an algorithm, improved from the one we used on Hi-C data (Testa et al 2013), which allows us to automatically detect rapid moss variability in AIA timeseries. We are currently working on applying this algorithm to AIA datacubes co-aligned with IRIS data (already available on the IRIS data search webpage 3 ), to automatically find these brightenings in IRIS spectral data.…”
Section: Discussionmentioning
confidence: 99%
“…Bidirectional reconnection outflows can cause line broadening, which IRIS has provided tantalizing glimpses of in slow (30 min cadence, 60s exposure) rasters of moss (Testa et al 2016), but firm evidence remains lacking because of observational limitations. Observations of the upper TR moss also have revealed signatures of the deposition and thermalization of non-thermal electrons generated by reconnection (Testa et al 2014;Testa et al 2020), but at the currently observed resolution of the corona, it remains unclear how common such events are (Graham et al 2019).…”
Section: Outstanding Challenges In Understanding Coronal Heatingmentioning
confidence: 99%
“…The hot emission of coronal loops in the active region core, in non-flaring conditions, is typically observed to be transient (e. (Graham et al 2019), at the footpoints of these AR core loops in their initial heating phases. IRIS spectral observations of these footpoint brightenings have provided new diagnostics of particle acceleration in nanoflares and NTE properties (Testa et al 2014;Testa et al 2020).…”
Section: Hot Loops and Footpoint Diagnostics Of Non-thermal Particlesmentioning
confidence: 99%
“…This means that the total energy deposited into the corona by these small-scale flares is even higher than that by large-scale flares and may even be responsible for coronal heating (Hudson 1991). Microflares are also found to be closely associated with other small-scale activities such as UV bursts (Peter et al 2014), coronal bright points , and hot loops in moss regions (e.g., Graham et al 2019;Testa et al 2020). These phenomena can be best discriminated and studied by extreme-ultraviolet (EUV) imaging and spectroscopic data.…”
Section: Introductionmentioning
confidence: 99%